O poético no cinema - Agra, Anacã Rupert Moreira Cruz e Costa (2011)
In this thesis, we critically examine the theories of the poetic text as proposed by Roman Jakobson and Jean Cohen and Michael Riffaterre so as to recognize, from a conciliation of the three theories, a generic model of the poetic concept so as to apply such a model to the cinema. Based also on filmic theories (drawn mainly from Marcel Martin and Yuri Lotman), we investigate how the poetic dimension gets materialized in narrative fiction feature films. From the establishment of a generic model of the poetic mechanism, having verbal poetry as a parameter, we study some particular modes of the poetic configuration in the cinema, elaborating through a wide range of filmic sequences, a series of tropes that constitutes a theoretical-didactic model for the analysis of poetic resources in the cinema.